Evaluation of the Relationship Between Systemic Hypertension and Subfoveal Choroidal Thickness Using Optical Coherence Tomography in Pediatric Patients - Fatoş Alkan; Semra Şen; Ercüment Çavdar; Hüseyin Mayalı; Şenol Coşkun (Galenos Publishing House, 2022)
Objective: Hypertension (HT) can cause vascular and microvascular changes. There is no barrier between systemic blood and ocular region. Changes in choroidal perfusion pressure due to HT may impair retinal function and oxygenation, and subfoveal choroidal thickness (SCT) may be affected by these changes. The aim of this study was to evaluate the effect of arterial HT on SCT in children. Method: The study was performed on 102 cases (51 patients and 51 controls), prospectively. Optical coherence tomography was used for the measurement of SCT and mean values of 3 consecutive measurements were evaluated. All cases had blood pressure measurements during all day via ambulatory blood pressure monitoring. Also, both groups were evaluated for the target organ damage. Results: There were 51 cases in patient group with the average age of 14.4+-2.8 years, and the rest of 51 control cases were meanly 14.5+-2.8 years in age (p=0.980). SCT was measured thinner in patients with target organ damage than the cases without target organ damage (p=0.027). SCT measurements of patients and control cases were not statistically significant different (p=0.569). Especially SCT was statistically significantly thinner in cases with increased left ventricular mass, left ventricular mass index and hypertensive nephropathy (p=0.02, p=0.00, p=0.039, respectively). Conclusion: Choroidal thickness decreases in patients with HT who develop target organ damage. Therefore, close follow-up of hypertensive patients with appropriate life changes and medical treatments is important before target organ damage develops.